Analysis of Teacher Readiness in the Implementation of the Independent Curriculum in SDN Serut Baru Gedangsari Gunungkidul - Arief, Ardian; Khasanah, Aprilia Devi Nur; Taryatman, Taryatman; Rahim, Abdul (Universitas Sarjanawiyata Tamansiswa, 2023)
Teacher readiness is important in implementing the independent curriculum. The purpose of this study is to describe teacher readiness and find out the supporting factors and obstacles faced by the teachers in the implementation of the independent curriculum at SDN Serut Baru Gedangsari Gunungkidul with a descriptive qualitative research design. Determination of data sources is done through purposive sampling techniques. Data collection techniques are carried out through interviews, observation, and documentation. Test the validity of the data using triangulation techniques. The results showed that; 1) teacher readiness in the implementation of the independent curriculum is not fully prepared based on the indicators of the four policies of the independent curriculum (AKM and UN substitute Character Survey, National Assessment instead of USBN, summary RPP, and zoning PPDB); 2) supporting factors in the implementation of the Independent Curriculum, namely clear regulations, PMM accounts, school readiness, and adequate learning infrastructure; 3) obstacles faced in the implementation of the independent curriculum, the teachers have not understood the independent curriculum as a whole, the Pancasila student profile project and differentiated learning have not been implemented, also the school facilities are inadequate. Strategies to overcome these obstacles by continuing to study the independent curriculum and implementing the independent curriculum according to the capacity of the teachers, students, and schools. What is needed to implement an independent curriculum needs support from various parties, so that the objectives of this independent curriculum can be achieved properly and realized at all levels in the elementary schools.